Wonders will never cease: Prospects for a new economy in Europe - Christopher Hurst; Kristian Uppenberg (EIB Papers, 2001)
The late 1990s saw one of the most rapid diffusions of a new technology seen in history. Within the space of 5 years the number of Internet users reached 50 million. This compares with the 13 years required by TV to reach the same number of users in the 1950s and 1960s, and the 40 years that radio took in the first half of the 20th century. Coupled with the rapid spread of Internet came a speculative bubble in high-tech companies. Throughout the last five years of the 1990s, some USD 150 billion were raised by US Internetrelated companies via venture capital injections and IPOs. It has now become the common view that much of this was a transfer of wealth from foolish investors to the staff of 'dot-coms', and the customers and advisors of these companies, rather than investment properly said. However, at the time it seemed that a new industrial revolution was underway.
Keywords: 330; Strukturwandel; Informationstechnik; Internet; Wirtschaftswachstum; EU-Staaten